STRATEGI SEKOLAH DALAM UPAYA PENCEGAHAN BULLYING DI ISMAELIYAH SCHOOL - Prasetio, Arif; Fanreza, Robie (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Bullying or bullying is not a trivial case. Cases that often occur among students, from the elementary stage to entering college. (Astuty) Cases of bullying are of particular concern to the world, particularly in developed and developing countries. This is what triggers and hinders the student learning process. Bullying or bullying has a very dangerous negative impact on victims, which can lead to death. This study aims to find out what strategies are used by schools in preventing bullying at Ismaeliyah School, Thailand. This research method uses a qualitative approach with descriptive methods. Data collection techniques by conducting interviews and observations. The subjects of this study included school principals, guidance and counseling teachers, and moral creed teachers. As for the process of implementing school efforts to prevent bullying at Ismaeliyah Trang School, Thailand which was carried out by researchers in the field, the school's efforts to prevent bullying were carried out in an orderly manner.